Safety and Use of Anticoagulation After Aortic Valve Replacement With Bioprostheses: A Meta-Analysis. (May 2016) - Riaz, Haris; Alansari, Shehab Ahmad Redha; Khan, Muhammad Shahzeb; Riaz, Talha; Raza, Sajjad; Luni, Faraz Khan; Khan, Abdur Rahman; Riaz, Irbaz Bin; Krasuski, Richard A.
Abstract : Background—: The American College of Cardiology guidelines recommend 3 months of anticoagulation after replacement of the aortic valve with a bioprosthesis. However, there remains great variability in the current clinical practice and conflicting results from clinical studies. To assist clinical decision making, we pooled the existing evidence to assess whether anticoagulation in the setting of a new bioprosthesis was associated with improved outcomes or greater risk of bleeding. Methods and Results—: We searched the PubMed database from the inception of these databases until April 2015 to identify original studies (observational studies or clinical trials) that assessed anticoagulation with warfarin in comparison with either aspirin or no antiplatelet or anticoagulant therapy. We included the studies if their outcomes included thromboembolism or stroke/transient ischemic attacks and bleeding events. Quality assessment was performed in accordance with the Newland Ottawa Scale, and random effects analysis was used to pool the data from the available studies. I 2 testing was done to assess the heterogeneity of the included studies. After screening through 170 articles, a total of 13 studies (cases=6431; controls=18210) were included in the final analyses. The use of warfarin was associated with a significantly increased risk of overall bleeding (odds ratio, 1.96; 95% confidence interval, 1.25–3.08; P <0.0001) or bleeding risk at 3 months (odds ratio, 1.92; 95% confidence interval, 1.10–3.34; P <0.0001) compared with aspirin or placebo. With regard to composite primary outcome variables (risk of venous thromboembolism, stroke, or transient ischemic attack) at 3 months, no significant difference was seen with warfarin (odds ratio, 1.13; 95% confidence interval, 0.82–1.56; P =0.67). Moreover, anticoagulation was also not shown to improve outcomes at time interval >3 months (odds ratio, 1.12; 95% confidence interval, 0.80–1.58; P =0.79). Conclusions—: Contrary to the current guidelines, a meta-analysis of previous studies suggests that anticoagulation in the setting of an aortic bioprosthesis significantly increases bleeding risk without a favorable effect on thromboembolic events. Larger, randomized controlled studies should be performed to further guide this clinical practice. Abstract : Supplemental Digital Content is available in the text.